A Biochanina A por via tópica promove efeitos anti-inflamatórios e antioxidantes no edema de orelha em camundongos - Santos Junior, Edson dos (2024)
The inflammatory process involves a succession of events that take place in the injured tissue. Although necessary, if exacerbated, the inflammatory process can lead to harmful effects. Inflammatory conditions are treated with anti-inflammatories, which can trigger adverse effects. Therefore, natural products are alternatives to new compounds with anti-inflammatory activity. In this sense, Biochanin A (BCA) is an isoflavone with anti-inflammatory and antioxidant effects, demonstrated in several disease models, however, never tested topically. Therefore, the objective of the research was to evaluate the anti-inflammatory potential of BCA topically, in a model of acute skin inflammation. To this end, female Swiss mice (n=7) were subjected to ear edema induced by TPA (12-O-tetradecanoylphorbol acetate), and treated with BCA (0.1, 0.3, 1 and 3mg/ear) or dexamethasone (DEXA). Anti-inflammatory activity was evaluated by determining the activity of myeloperoxidase (MPO), proinflammatory cytokines, such as TNF-α, IL-6, IL-1β and histopathological analysis. Furthermore, oxidative damage was evaluated by the dosage of substances reactive to thiobarbituric acid (TBARS) and antioxidant protection, by sufridil groups (NP-SH). It was observed that treatment with BCA, at a dose of 3mg/ear, promoted the greatest reduction in edema among the doses tested, in addition to reducing MPO, concentration of the evaluated cytokines and TBARS. Furthermore, the NP-SH groups increased, equivalent to the DEXA group. In histological analysis, the BCA and DEXA groups reduced interstitial edema and inflammatory infiltrate equally, compared to TPA. Thus, the present work demonstrated that BCA has anti-inflammatory and antioxidant activity in acute skin inflammation, when administered topically.